Medical Literature Searches -How Many Bibliographic Databases are Needed for Sufficient Retrieval in Medical Topics? - John, K. (Methods of Information in Medicine, 1985)
As many bibliographic services in medicine are offered, literature searches in eight databases at DIMDI were performed to find out which database is most important in medicine. The distribution of publications from members of the medical faculty of Frankfurt University was examined. No save prediction is possible as to which database will yield most articles. Overlapping from different databases is often rather low. The selection of an appropriate database mix for sufficient recall and in a cost-effective manner.is a task for an experienced searcher.
Keywords: Medicine; Literature Search; Database Comparison; Overlapping